FATWA SHEIKH Aá¸¤MAD KHAá¹¬ÄªB AL-MINANGKABÄ€WÄª (DS 0003 00018): A JÄwÄ« Ulama’s Response to the Heterodoxy of Sufism - Rohmana, Jajang A (IAIN Ponorogo, 2023)
This article discusses the fatwa of a JÄwÄ« or Malay-Indonesian archipelago ulama who taught in Mecca in the early twentieth century, Sheikh Ahmad Khatib Minangkabau (1860-1916). He was issuing fatwa on heterodox sufism in the archipelago. His fatwa is written in a manuscript from Ogan Komering Ilir entitled Fatwa Sheikh Aá¸¥mad Khaá¹Ä«b al-MinangkabÄwÄ« (DS 0003 00018). The manuscript has been digitized by DREAMSEA in 2019. This manuscript was probably written when he became a lecturer in Mecca between 1887-1914. It contains questions and answers about the existence of the name Muhammad and rÅ«á¸¥ al-quds (holy spirit) in the human heart that commands the body. Using a social history approach, this study shows that the Fatwa manuscript shows the response of JÄwÄ« ulama who were increasingly influenced by the teachings of Islamic reformism. Ahmad Khatib stated that it was impossible for the spirit of Muhammad and rÅ«á¸¥ al-quds to exist in the body. For him, Muhammad is a human being and the holy spirit is Gabriel, an angel. He stated that whoever believes that both Muhammad and Gabriel are in his/her body is wrong and misguided, and if he/she believes that they are eternal, then he/she is a disbeliever. Ahmad Khatib’s fatwa indicate an attempt to purge the heterodoxy of sufism continually by SunnÄ« ulama in the early twentieth century.